Pollination of Cucurbita spp. (squash and pumpkin) crops in Florida - Rachel E. Mallinger; Oscar E. Liburd (EDIS)
Squash and pumpkin (Cucurbita spp.) are economically significant crops in Florida with over 7,900 acres in production and an estimated value of $35,412,000. Without insect pollination, however, crop yields for zucchini, crookneck, spaghetti, butternut and the rest of the large and delectable crew of squash and pumpkin species grown in Florida would be low to nonexistent. This 7-page fact sheet written by Rachel E. Mallinger and Oscar E. Liburd and published by the UF/IFAS Entomology and Nematology Department explains the pollination biology and requirements for squash and pumpkin, describes the signs and causes of poor pollination, and provides recommendations for improving pollination of these crops in Florida.<